Will Food Be Affordable to Filipinos by 2030? Alternative Expenditure Policies toward Ending Hunger by 2030 - Roehlano M. Briones; Howarth E. Bouis; Imelda Angeles-Agdeppa; Isabel B. Espineli; Ma. Lynell V. Maniego (Philippine Institute for Development Studies (PIDS), 2023)
The current inflationary period has placed the spotlight on hunger and food insecurity, as the current Philippine Development Plan has strongly emphasized the attainment of food affordability for all Filipinos. This study offers a scenario analysis using computable general equilibrium modeling of household purchasing power and affordability of a diet with sufficient energy, protein, and Vitamin A. Scenarios posited are as follows: Reference scenario, which projects forward from recent past trends; the Subsidy scenario, based on producer support; and Productivity, which is a long-term government investment focusing on general services. The scenario analysis finds the following: Under current economic trends, most Filipino households will be able to afford adequate levels of energy and protein by 2030, but not Vitamin A. The Reference scenario is also associated with higher relative consumer and producer prices, as well as far greater levels of output. Despite attenuation of sharp changes in the consumer price of Rice & corn, changes in energy/nutrient intakes under the Subsidy scenario are just equal to those of the Reference scenario. The Productivity scenario entails significantly faster increases in energy, protein, and Vitamin A intake compared with the previous scenarios. The Productivity scenario also leads to smaller changes in price and greater changes in quantity compared with the other scenarios. Implications for policy may be summarized as follows: a) Maintaining overall growth in the range of 5 - 6 percent per year is key to improving diet quality and thereby an affordable energy- and protein-sufficient diet; b) The slightly favorable impact of rice subsidies on the price of rice and on energy/nutrient intake of households may not be worth the added risk of fiscal instability; c) The scenario analysis tend to justify investing in general services such as R&D and infrastructure, as the preferred strategy to achieving affordable diets.
Keywords: 330; computable general equilibrium; food security; scenario analysis; agricultural subsidy; producer support; general services support